(untitled) (Journal of Political Science and International Relationship, 2025)
Charter change is a contentious civic issue that resurfaces with every administration in Philippine politics. Despite this, limited empirical studies explored the awareness and attitudes of the Filipino youth, a growing and influential electorate, toward charter change. This study examined the awareness and attitudes on charter change among 133 Humanities and Social Sciences (HUMSS) senior high school (SHS) Filipino students at the largest government-funded secondary school in the Eastern Visayas region to address the scarcity in understanding how Filipino youth perceive constitutional reform. The study utilized a 5-point Likert scale questionnaire, employing descriptive bivariate correlational and comparative designs and proportionate stratified sampling, followed by a systematic random sampling within strata. The results revealed that students exhibited moderate awareness and neutral attitudes toward charter change. Spearman’s correlation analysis further indicated a strong, positive, and significant relationship between awareness and attitudes, suggesting that higher awareness is associated with more favorable attitudes. Mann-Whitney U test found no significant differences in awareness and attitudes across demographic groups (grade level, age, sex, leadership positions, political affiliations, and community type). This study highlights the importance of promoting civic education and political literacy among Filipino youth to cultivate informed engagement in constitutional matters. Rather than signaling apathy, the Filipino youth’s ambivalence reflects the intricacy of political discourse and a need for more accessible, contextualized engagement with national issues.